Вплив скiнченого радiуса Лармора на дифузiю пробних частинок - Cherniak, O. M.; Zasenko, V. I. (Publishing house "Academperiodika", 2018)
Particle diffusion in a static random electric field across a uniform magnetic field is considered. Earlier, we have proposed the closure for the statistical equation that describes particle diffusion in the drift approximation with account for the effect of particle trapping. Here, a generalization of our approach for a finite Larmor radius is given. It is shown that the statistical characteristics of a particle ensemble found as solutions of the analytical model are consistent with the results of direct numerical simulations within a wide range of Larmor radii.